RNA Pol-II transcripts in nucleolar associated domains of cancer cell nucleoli - Soumya Roy Chowdhury; Arunima Shilpi; Gary Felsenfeld (Nucleus)
We performed a comparative study of the non-ribosomal gene content of nucleoli from seven cancer cell lines, using identical methods of purification and analysis. We identified unique chromosomal domains associated with the nucleolus (NADs) and genes within these domains (NAGs). Four cell lines have relatively few NAGs, which appears mostly transcriptionally inactive, consistent with literature. The remaining three lines formed a separate group with nucleoli with unique features and NADS. They constitute larger number of common NAGs, marked by ATAC-seq and having accessible promoters, with histone markers for transcriptional activity and detectable RNA Pol II bound at their promoters. The transcripts of these genes are almost entirely exported from the nucleolus. These results indicate that RNA Pol II dependent transcription in NADs can vary widely in different cell types, presumably dependent on the cell’s developmental stage. Nucleolus-associated genes are likely to be distinguished marks reflecting the cell’s metabolism.